STUDI INTERAKSI ION LOGAM Mn2+ DENGAN SELULOSA DARI SERBUK KAYU - Mohadi, Risfidian; Saputra, Adi; Hidayati, Nurlisa; Lesbani, Aldes (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014DO - 10.24843/JCHEM.2014.v08.i01.p01, 2014)
Separation of cellulose from sawdust using methanol and hydrocloric acid in various acid concentrations has been carried out. Cellulose from sawdust was characterized using FT-IR Spectroscopy and XRD difractometer. The cellulose was used as adsorbent for Mn 2+ and Co 2+ metal ions in aqueous medium. Adsorptions process was studied through variation of time interaction, concentration and separation desorption. FT-IR Spectrum shows that cellulose with 5% acid concentration has similarity with FT-IR cellulose standard. The XRD difractometer pattern of cellulose shows that cellulose has amorf structure. The adsorption rate constant of Mn 2+ on cellulose from sawdust shows adsorption rate constant in cellulose is higher than in sawdust. Adsorption energy of Mn 2+ metal ion in cellulose from sawdust was about 26.21 kJ/mol. The adsorption capacity of Mn 2+ in cellulose is higher than in sawdust. The desorption of Mn 2+ metal ion using H 2 O, Na-EDTA, Amonium acetic, and HCl shows that the adsorption mechanism of Mn 2+ on cellulose and sawdust is dominated by chemical interaction.
Keywords: cellulose, Mn metal ion, adsorption, desorption